A Year Down Yonder - Richard Peck (New York, United States Scholastic, 2000)
Winner of the Newbery Medal "Peck charms readers once again with this entertaining sequel to A Long Way from Chicago"--School Library Journal (starred review) It was within the pages of Richard Peck's Newbery Honor-winning A Long Way from Chicago that Mary Alice and Grandma Dowdel first made their captivating debut. Now they're back for more astonishing, laugh-out-loud tales when fifteen-year-old Mary Alice moves in with her spicy grandmother for the year. Expect moonlit schemes, romances both foiled and founded, and a whole parade of fools made to suffer in unusual (and always hilarious) ways. Wise, exuberant, and slyly heartwarming, this is a satisfying companion to Grandma Dowdel's adventures in A Long Way from Chicago and A Season of Gifts. Newbery Medal Winner ALA Best Book for Young Adults ALA Notable Book Booklist Best Books of the Year School Library Journal Best Books of the Year New York Times Best Seller "Audience members will breathe a sigh of regret when the eventful year "down yonder" draws to a close."--Publishers Weekly (starred review) "Wit, gentleness, and outrageous farce."--Booklist (starred review)
Keywords: Realistic Fiction -- Realistic Fiction